Coordination-Induced Spin-State Change in Manganese(V) Complexes: The Electronic Structure of Manganese(V) Nitrides - Kropp, Henning; Scheurer, Andreas; Heinemann, Frank Wilhelm; Bendix, Jesper; Meyer, Karsten (Inorganic Chemistry, 2015)
This work illustrates that manganese(V) nitrido complexes are able to undergo a coordination-induced spin-state change by altering the ligand field from trigonal to tetragonal symmetry. For the reversible coordination of acetonitrile to trigonal [(TIMENxyl)Mn(N)]2+ (1; high-spin S = 1; with TIMENxyl = tris[2-(3-xylylimidazol-2-ylidene)ethyl]-amine), a temperature-dependent coordination-induced spin-state switch is established. Starting from the manganese(V) nitrido complex 1, the synthesis and characterization of a series of octahedral, low-spin (S = 0) manganese(V) nitrido complexes of the type [(TIMENxyl)Mn(N)(L)]n+ (L = MeCN (2), tBuNC (3), CN– (4), NCS– (5), F– (6), μ-Ag(CN)2− (7), with n = 1, 2) is described. These represent the first examples of d2 transition metal complexes showing a coordination-induced spin-state change. Spectroscopic, as well as ligand-field theory and density functional theory studies suggest a transition from a 2 + 2 + 1 orbital splitting in the trigonal case to a 1 + 2 + 1 + 1 splitting in tetragonal symmetry as the origin of the coordination-induced spin-state change.